2015
DOI: 10.17344/acsi.2015.1558
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Assisted Sonochemical Synthesis and Characterization of Gadolinium Doped Zinc Oxide Nanoparticles

Abstract: Pure and Gd doped Zinc Oxide (ZnO) nanoparticles were synthesized by sonochemical method using different surfactants (PVP/CTAB). The nanoparticles were characterized by powder X-ray diffraction (PXRD), Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), particle size analysis by DLS technique and UV-Visible spectroscopy. The effect of Gd doping and nature of surfactants on crystallite size, morphology and band gap of ZnO nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 29 publications
(30 reference statements)
1
1
0
Order By: Relevance
“…Out of 595 cases, 74% were found in large intestine, 25% in the gastric region while only 1% was present in small intestine. Similar results were reported by Khujuria et al [12] from northern part of India wherein, they reported that the maximum number of polyps were present in large intestine (78.43 %) followed by stomach with 16.67%. Determining the prevalence of gastrointestinal neoplasms in various anatomical sites can be an important factor to select the favorable modality of screening.…”
Section: Discussionsupporting
confidence: 89%
“…Out of 595 cases, 74% were found in large intestine, 25% in the gastric region while only 1% was present in small intestine. Similar results were reported by Khujuria et al [12] from northern part of India wherein, they reported that the maximum number of polyps were present in large intestine (78.43 %) followed by stomach with 16.67%. Determining the prevalence of gastrointestinal neoplasms in various anatomical sites can be an important factor to select the favorable modality of screening.…”
Section: Discussionsupporting
confidence: 89%
“…The decrease in the energy density values is ascribed to the splitting of the energy levels and hence the decrease in bandgap of the materials. by Heena et al and Murmu et al [43,44]. The grain size (GS) was estimated from the histogram distribution curve as indicated in figures 3(a)-(f).…”
Section: Resultsmentioning
confidence: 99%
“…It has been found that the type of source of the inner transition metal and amino acids has an influence on the shape and grain size of the nanocomposite [13,14]. It was further observed that different types of organic fuels (urea and alanine or their mixture) have an influence on the temperature of combustion, crystallographic structure, morphology and resulting particle sizes [6]. It has also been found that the particle size increased with increasing calcination temperature in the combustion synthesis (from 25 nm at 800 ºC to 200 nm at 1100 ºC) [4].…”
Section: Introductionmentioning
confidence: 97%
“…Among the important lanthanides oxides, Gd2O3 gains a significant importance due to its good crystallographic stability up to 2325 °C, high mechanical strength, and excellent thermal conductivity together with relatively high dielectric constant, wide band gap [2], and versatile and tunable magnetic properties [3]. Nanomaterials based on Gd2O3 have been used for example in the solid-state lasers [4], in the solid oxide fuel cells as an electrolyte [5], in the temperature sensors [6] or as the contrast agents in the magnetic resonance imaging [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation